Implementation of the Value of Tolerance in the Community of The Cireundeu Traditional Village - Fauziyyah, Firas (Universitas Pendidikan Indonesia (UPI), 2022)
Indonesia as a multicultural country is a representative of the Indonesian people who are diverse and have characteristics in each region. One of the diverse characteristics of Indonesian society is shown by the differences in religion and beliefs that are believed by the Indonesian people, until now there are still Indonesian people who believe in traditional teachings, one of which is believing in Sunda Wiwitan. This study uses a qualitative approach with ethnographic methods. The data obtained by the researchers used interview, observation, and documentation techniques to the respondents who were taken using snowball sampling technique. The results of this study indicate that there is a developed tolerance value in the Cireundeu traditional village community, including the value of mutual assistance, the value of mutual respect and respect, the value of nationalism, the value of non-discrimination, and the value of independence and accepting differences. The form of the implementation of tolerance is shown by the involvement in various events at the Cireundeu traditional village. The driving factors for tolerance are ties of kinship and the influence of the role of parents when providing early education about the diverse environment of the Cireundeu traditional village community and the role of parents to set an example for their children through habituation to be actively involved in various events of the Cirendeu traditional village community.